2005
DOI: 10.1111/j.1471-8286.2005.00905.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of polymorphic microsatellites in Labeo rohita and their cross‐species amplification in related species

Abstract: The major Indian carps namely rohu (Labeo rohita), catla (Catla catla), mrigal (Cirrhinus mrigala) and calbasu (Labeo calbasu) are important freshwater species of the Indian subcontinent constituting over 65% of the fish produce. In the present study, isolation of 12 microsatellite loci from rohu has been reported. Cross‐species amplification in related carps and their implication in population genetic studies as well as selective breeding program were discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 3 publications
4
29
1
Order By: Relevance
“…gov). For cross-species amplification of microsatellite loci, a total of 40 microsatellite primers from Catla catla [24]; Cyprinus carpio [25,26]; Barbodes gonionotus [27]; Campostoma anamalum [28]; Labeo rohita [29] and Pimephales promelas [30] were used ( Table 1). The crossspecies amplification trials were done with eight specimens of G. curmuca and of the 40 primer pairs tested, 34 (85 %) provided successful amplification of homologous loci in G. curmuca.…”
Section: Pcr Amplification and Selection Of Microsatellite Locimentioning
confidence: 99%
“…gov). For cross-species amplification of microsatellite loci, a total of 40 microsatellite primers from Catla catla [24]; Cyprinus carpio [25,26]; Barbodes gonionotus [27]; Campostoma anamalum [28]; Labeo rohita [29] and Pimephales promelas [30] were used ( Table 1). The crossspecies amplification trials were done with eight specimens of G. curmuca and of the 40 primer pairs tested, 34 (85 %) provided successful amplification of homologous loci in G. curmuca.…”
Section: Pcr Amplification and Selection Of Microsatellite Locimentioning
confidence: 99%
“…Again in these same four loci the average observed heterozygosity and expected heterozygosity were 0.746 and 0.621 (Das et al, 2005) and 0.413 and 0.493 (Alam et al, 2009) in the Indian major carp populations. We observed that average observed heterozygosity and expected heterozygosity was lower than that of obtained in the study by Das et al (2005) but higher than that of obtained by Alam et al (2009).…”
Section: Discussionmentioning
confidence: 90%
“…Khan et al (2006) using allozyme marker reported 27 % polymorphic loci in the three river population of L. rohita. Das et al (2005) Nei's (1972) developed microsatellite markers obtained all the studied loci polymorphic in an Indian farmed population of L. rohita. Using four loci they obtained a total of 20 alleles (5 alleles in average) and Alam et al (2009) obtained only 14 alleles, while we obtained 20 alleles by using three loci.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But earlier, using same loci, Das et al, (2005) found the observed heterozygosity to be higher than expected heterozygosity in the Indian population of L. rohita which is in accordance to the present findings and these results can be due to the fact that several evolutionary forces like random genetic drift, migration, mutation and their mutual interactions act on the wild populations and influence the pattern of genetic differentiation (Avise, 1994). Charlesworth and Charlesworth, (2016) also suggested that the polymorphism present in natural populations differs markedly in different species and also within the species.…”
Section: Microsatellite Based Genetic Variations Between the Populationsmentioning
confidence: 98%